EGFR-AS1/HIF2A regulates the expression of FOXP3 to impact the cancer stemness of smoking-related non-small cell lung cancer. (June 2019) - Qi, Haolong; Wang, Shanshan; Wu, Juekun; Yang, Shucai; Gray, Steven; Ng, Calvin S.H.; Du, Jing; Underwood, Malcolm J.; Li, Ming-Yue; Chen, George G
Background: Early data showed that FOXP3 could induce epithelial-mesenchymal transition by stimulating the Wnt/β-catenin signaling pathway in non-small cell lung cancer (NSCLC). However, how the expression of FOXP3 is regulated in NSCLC remains unknown. We thus explored the impacts of the long noncoding RNA EGFR antisense RNA 1 (EGFR-AS1) and hypoxia-inducible factor-2A (HIF2A) on FOXP3 expression and the cancer stemness of NSCLC. Methods: Lung tissues samples from 87 patients with NSCLC and two NSCLC cell lines were used in this study. The regulation of FOXP3 and lung cancer cell stemness by EGFR-AS1 and HIF2A was determined at molecular levels in NSCLC tissue samples and cultured cells in the presence/absence of the smoking carcinogen, 4-(N-methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK) (also known as nicotine-derived nitrosamine ketone). The results were confirmed in tumor xenograft models. Results: We found that NNK decreased the expression of EGFR-AS1 in the long term, but increased the expression of HIF2A and FOXP3 to stimulate lung cancer cell stemness. EGFR-AS1 significantly inhibited FOXP3 expression and NSCLC cell stemness, whereas HIF2A obviously promoted both. The enhancement of lung cancer stemness by FOXP3 was, at least partially, via stimulating Notch1, as the inhibition of Notch1 could markedly diminish the effect of FOXP3. Conclusions: FOXP3, the expression of which is under the fine control of EGFR-AS1, is a critical molecule that promotes NSCLC cancer cell stemness through stimulating the Notch1 pathway.